Die Spannung zwischen Zentralismus, Föderalismus und Regionalismus als Grundzug der politisch-geographischen Entwicklung Deutschlands bis zur Gegenwart - Schöller, Peter (ERDKUNDE, 1987)
Beginning with the “Holy Roman Empire of the German Nation - a realm lacking a permanently fixed capital in Central Europe - German particularism, with its marked tendency towards small individual states, is not primarily evaluated in a negative way but considered on its own historical merit as a development with advantages and disadvantages. The first major point of this paper deals with the numerous capitals and residential cities in Germany, which are here - for the first time - presented in maps showing their distribution and ranking with regard to cultural influence. After the politico-geographical “consolidation” during the period of the French occupation, the empire created by Bismarck grew out of extreme forms of a federation of states. The Weimar period with its federal constitution gave way to the over-centralization of the Hitler regime. After the end of the Second World War the formation of German Lander in the Soviet sphere of influence persisted only from 1945 to 1952. The Federal Republic of Germany, on the other hand, arrived at a federal system, which is now supported by the majority of its citizens as relevant to their concerns and as a balance against too powerful a centralism. An attempt at a well-grounded reorganisation of the federal territory, which had been planned in Article 29 of the Constitution (Grundgesetz) did not meet with success. The author reports on the two attempts at reorganisation in which he was involved, first as an independent academic member of the , Luther Commission in 1955, and later as a member of the “Ernst Commission, an expert commission set up by the Federal Government in 1972. Finally, the author gives his support to continued development of regionalism in the Federal Republic of Germany.